Circulating biomarkers of inflammaging as potential predictors of COVID-19 severe outcomes. (June 2022) - Sabbatinelli, Jacopo; Matacchione, Giulia; Giuliani, Angelica; Ramini, Deborah; Rippo, Maria Rita; Procopio, Antonio Domenico; Bonafè, Massimiliano; Olivieri, Fabiola
Abstract: The COVID-19 pandemic caused by SARS-CoV-2 infection has been of unprecedented clinical and socio-economic worldwide relevance. The case fatality rate for COVID-19 grows exponentially with age and the presence of comorbidities. In the older patients, COVID-19 manifests predominantly as a systemic disease associated with immunological, inflammatory, and procoagulant responses. Timely diagnosis and risk stratification are crucial steps to define appropriate therapies and reduce mortality, especially in the older patients. Chronically and systemically activated innate immune responses and impaired antiviral responses have been recognized as the results of a progressive remodeling of the immune system during aging, which can be described by the words 'immunosenescence' and 'inflammaging'. These age-related features of the immune system were highlighted in patients affected by COVID-19 with the poorest clinical outcomes, suggesting that the mechanisms underpinning immunosenescence and inflammaging could be relevant for COVID-19 pathogenesis and progression. Increasing evidence suggests that senescent myeloid and endothelial cells are characterized by the acquisition of a senescence-associated pro-inflammatory phenotype (SASP), which is considered as the main culprit of both immunosenescence and inflammaging. Here, we reviewed this evidence and highlighted several circulating biomarkers of inflammaging that could provide additional prognostic information to stratify COVID-19 patients based on the risk of severe outcomes. Highlights: Immunosenescence and inflammaging are emerging risk factors for the development of COVID-19 severe outcomes. Markers of NETosis – the program for formation of neutrophil extracellular traps – are increased in COVID-19. COVID-19 thrombotic complications result from activation of immunothrombosis and dysfunction of the coagulation system. Inflammaging and immunosenescence biomarkers should be implemented into clinical practice for predicting COVID-19 prognosis.